Urban sustainability in Brazil and its applications: a systematic review - Leal, Thomas Leonardo Marques de Castro; Silva, Tâmara Bastos; Figueirêdo, Sheilla da Silva Melo; Lopes, Wilza Gomes Reis; Zanella, Maria Elisa (National Journal of City Management, 2022)
The depletion of natural resources has stimulated debates on urban sustainability. Thus, this paper aims to analyze articles on urban sustainability in Brazilian territory, as well as its instruments and indicators. To achieve the proposed aim, this work uses the systematic review method. The studies on urbanization arise as legitimators of a process of modernity and industrialization. Thus, the theme “urban sustainability” gained notoriety when it was introduced in the 17 Sustainable Development Goals. Many studies analyzed used indicators, with a quantitative and/or qualitative approach, with various applications, among cities, neighborhoods, and even projects. In Brazil, there is a legal framework that favors the development of urban sustainability. However, it is necessary to use adequate methodologies to reduce the subjectivity of sustainability assessment. One of the major difficulties in applying urban sustainability assessment is data availability.